2001
DOI: 10.1097/00006842-200105000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Normalization of Hypertensive Responses During Ambulatory Surgical Stress by Perioperative Music

Abstract: The perceived stress of ambulatory surgery in geriatric patients is associated with a clinical hypertensive response that is ameliorated by self-selected perioperative music, which also decreases perceived stress and increases patients' sense of personal control and well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(47 citation statements)
references
References 16 publications
0
45
1
1
Order By: Relevance
“…Other studies have provided evidence to support the notion that the effects of music or sound as modulators of human response to surgical stress are also significant in unconscious patients under general anaesthesia [2,12,13]. Intervention with music or sound intra-operatively can decrease sedative and analgesic requirements, blunt haemodynamic change, reduce postoperative pain, and improve postoperative recovery [1,2,4,6,13].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Other studies have provided evidence to support the notion that the effects of music or sound as modulators of human response to surgical stress are also significant in unconscious patients under general anaesthesia [2,12,13]. Intervention with music or sound intra-operatively can decrease sedative and analgesic requirements, blunt haemodynamic change, reduce postoperative pain, and improve postoperative recovery [1,2,4,6,13].…”
Section: Discussionmentioning
confidence: 97%
“…It has been recommended that peri-operative stress control programmes should include both pharmacological and non-pharmacological methods, used either alone or in combination [2][3][4]. Music has been shown to reduce patients' anxiety and decrease sedative requirements [1,[4][5][6].…”
mentioning
confidence: 99%
“…This is mostly investigated in a perioperative setting or in patients undergoing endoscopic procedures [20][21][22][23]. Because of this effect, choosing music as our control group enabled us to differentiate between the effect of listening to music (the Resperate produces musical tones as well) and the effect of reducing breathing frequency on BP.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that music eases stress responses psychologically, physiologically, and endocrinologically. It is well known that listening to music reduces uneasiness (Gerdner & Swanson, 1993;Kaminski & Hall, 1996), depression, and fatigue (Field et al, 1997;Hanser & Thompson, 1994), changes mood (Cadigan et al, 2001;Gfeller & Lansing, 1991;McCraty et al, 1998;Sousou, 1997), and suppresses pain (Allen et al, 2001;Browning, 2000;Maslar, 1986). However, some reports that compare listening to music with other relaxation methods show no differences in alleviation of anxiety, depression, and fatigue (Field et al, 1997;Hanser & Thompson, 1994) or reduction of heart rate (Guzzetta, 1989;Scheufele, 2000).…”
Section: Cortisolmentioning
confidence: 99%